The prevalence of Strongyloides stercoralis infection in rural population of Bali: A preliminary study (Medical Journal of Indonesia, 2001)
A cross-sectional study was carried out from March until September 1992 in 4 different geo-climatic rural villages in Bali to assess the prevalence of Strongyloides stercoralis infection related to age, gender and geo-climatic condition. The number of selected samples using multistage stratified random sampling based on age and gender was 2880. Strongyloides larvae in stool samples were identified by modified Harada Mori fecal culture technique. The results showed that the overall prevalence of Strongyloides infection was 1.6%; the prevalence in male was 1.2% and in female was 2.1%, however the gender difference was not statistically significant. In term of age, there was no statistically significant difference. The highest prevalence (2.4%) was found among 7-12 years children, followed by aged 7 years or less (1.6%), 18 years or over (1.6%), and 13-18 years (0.6%). The prevalence of Strongyloides infection related to geo-climatic conditions was significantly difference. The highest prevalence of Strongyloides infection was at wet highland (3.3%), followed by wet lowland (1.5%), dry highland (1.0%), and dry lowland (0.9%). In conclusion, the prevalence of Strongyloides stercoralis infection in Bali was very low. Prevalence of Strongyloides infection was highly related to geo-climatic type of area, but not to gender and age groups. (Med J Indones 2001; 10: 174-7)